Implicit Meanings of Jentaka Lyrics Song and Video Clip: A Semiotic Analysis - Meiyanti Nurchaerani; Alfian Alfian; Syahiid Hidayatullah R. Hartadhi; Christianto Christianto (Journey: Journal of English Language and Pedagogy, 2024)
This study analyzed the lyrics and music video of "Jentaka" by For Revenge using the semiotic approaches of Charles Sanders Peirce and Ferdinand de Saussure. This research used a qualitative approach with semiotic analysis methods. This approach was chosen because the research aimed to explore the meanings contained in the lyrics and music video of “Jentaka” by the band For Revenge. Through a qualitative approach, the researcher could understand and interpret the symbols and signs used in these media. The song depicted themes such as emotional suffering, identity duality, and self-introspection. The lyrics reflected the conflict between the external appearance of being an entertainer and the inner feelings of pain and sadness. Additionally, the inclusion of a Quranic verse from Surah Al-Ankabut, verse 64. The results of the study indicated that semiotic analysis could reveal complex layers of meaning in artistic works, offering a deeper understanding of the messages and themes conveyed by the artist. This research contributed to further comprehension of the use of signs and symbols in music and music videos as a medium of artistic communication.